Tantangan dan Peluang Pendidikan Literasi Digital Dalam Konteks Sdgs 2030 - Nurkamila, Agna; Rahmalia, Naila; Rachman, Ichsan Fauzi (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Abstract. Digital literacy education plays an important role in achieving the 2030 Sustainable Development Goals (SDGs), especially in supporting education quality, reducing disparities and promoting social inclusion. Key challenges in digital literacy education include gaps in access to technology and the internet, lack of adequate infrastructure, and digital skills gaps among different groups of people. Cultural barriers and resistance to change are also significant obstacles. However, great opportunities arise from the rapid development of technology, global initiatives to support digital education and the potential for collaboration between government, the private sector and civil society. Efforts to integrate digital literacy into formal and non-formal education curricula can accelerate the achievement of the SDGs, by enhancing the critical and adaptive skills needed in the digital age. This research explores these challenges and opportunities and provides strategic recommendations to optimize the role of digital literacy education in the context of the 2030 SDGs. Keywords: digital literacy, SDGs 2030, education, technology, social inclusion, digital skills.